DEVELOPING A CONTENT-BASED SYLLABUS FOR STUDY PROGRAM OF ANTHROPOLOGY FACULTY OF CULTURAL STUDIES UNIVERSITAS BRAWIJAYA - Dian Novita Dewi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
Abstract This study is intended to develop a content-based syllabus for Study Program of Anthropology (SPA) at Faculty of Cultural Studies Universitas Brawijaya since this study program has not had a syllabus for English course yet. The developmental research is implemented when conducting this study. In this study, the syllabus was developed by using the educational research and development (R & D) from modified Borg and Gall (1983)’s theory following five steps: (1) needs analysis, (2) syllabus development, (3) expert validation, (4) try-out, and (5) final product.The need analysis was conducted as the significant step in this research and therefore, it was done to find out the students’ needs and expectation in English course. The need survey was implemented to the fresh undergraduate students and the fifth semester students of SPA. The interview was also conducted to gain the exact situation need and the information on what those respondents expect to have syllabus of English course.The syllabus implemented in English course used content-based approach which in line with Anthropology field. Regarding to the content-based approach, the syllabus contains a set of topics related to Anthropology program’s outcome covering tourism, media, and East Indonesia. The topics were presented in sixteen meeting included 2 quizzes, mid-term test, and final semester test. Moreover, the materials and the learning strategies were given in each meeting in relation with the topics. The syllabus concerns to reading, writing and speaking skills which in relation with the program’s outcome. To make the valid syllabus, the syllabus was validated by the expert of ESP syllabus from Universitas Brawijaya. After validating, it is tried out to the controlled English class and then revised until it becomes the final product. The developed syllabus is designed by referring to the softskills on IQF’s parameters which are integrated in the learning strategies. The syllabus contains the course description, the course objective, the standard competence, the indicators, the learning objectives, the list of the topics or materials, the teaching strategies, the assessment, the teaching aids, and the time allotment. Moreover, the result of this study is accompanied by a unit sample and a lesson plan.Finally, for others who have interest in ESP syllabus, this syllabus can lead them to a further research either on different aspect of the same filed like developing English syllabus for Academic English 2 in SPA, or on other research development study in developing instructional materials.